ANALYSIS OF THE IMPACT OF COVID-19 ON THE CAPITAL OF RURAL BANKS (BPR) AND SHARIA RURAL BANKS (BPRS) IN THE JAVA-BALI REGION - Dian Panca Putra Nandika; Puji Harto (RADJA PUBLIKA, 2026)
The COVID-19 pandemic has put significant pressure on banking stability, including for Rural Banks (BPR) and BPRS, which are more vulnerable than commercial banks. This situation necessitates an understanding of how internal and external factors influence the capital strength of regional banks, particularly in the Java-Bali region, which has distinct economic dynamics. This study analyzes the factors influencing the Capital Adequacy Ratio (CAR) of Rural Banks (BPR) in the Java-Bali region during the 2019 Q4 – 2024 Q4 period. Using panel data of 180 BPRs and the Random Effects Model (REM) estimation method, this study examines the effects of COVID-19, regional characteristics (Bali dummy), profitability (ROA), operational efficiency (BOPO), bank size (log total assets), and market concentration (log HHI) on CAR. The results showed that Covid-19 had a negative and significant impact on CAR, indicating a weakening of the capital position of rural banks (BPRs) during the pandemic. Profitability had a positive effect on CAR, while operational inefficiency (high BOPO) and larger bank size were associated with lower CAR. Conversely, location (Bali) and market concentration variables did not show a significant effect. These findings confirm that BPRs' internal performance, particularly profitability, efficiency, and asset growth management, are key factors in strengthening capital buffers, while external shocks such as Covid-19 remain a risk that needs to be anticipated.